(untitled) (Bangladesh Critical Care Journal, 2022)
We described a case of an alcoholic patient who presented with a history of Jaundice for 25 days, generalised weakness and loss of appetite for 20 days and altered level of consciousness for 2 days. On examination, patient was grossly icteric and there were no palpable lymphnode. Central nervous system examination revealed low GCS (E2V2M3), Pupil bilaterally pin point, Planter extensor bilaterally and abdominal examination showed mild hepatomegaly. MRI of Brain showed symmetrical hyperintense areas on T2W and FLAIR images seen in the Mamillary bodies, dorsomedial thalami, tectal plate, periaqueductal area and around the third ventricle. The lesions are hypointense on T1W images and showed diffusion restriction on DW images. These findings are compatible with Wernickes Encephalopathy. He was started on thiamine supplementation with which neurological signs improved. Patient had a history of RTA about 1 month prior to ICU admission. Then he underwent Spleenectomy operation. Again a laparotomy operation was done due to intra-abdominal collection and repair of the omental vessels done with thorough peritoneal collection. It is important to consider Wernickes encephalopathy in alcoholic patients with intra-abdominal surgery Bangladesh Crit Care J September 2022; 10(2): 158-160